The political economy of global restructuring - Rima, Ingrid, H., Editor (Hants : Edward Elgar Publishing, 1993)
Volume 1. Economic organization and production. Volume II. Trade and finance
Keywords: Economic development; Economic policy -- Political aspects; European Economic Community; International finance; International trade